2019
DOI: 10.1016/j.jhep.2019.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Impact of combined selective internal radiation therapy and sorafenib on survival in advanced hepatocellular carcinoma

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
249
1
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 292 publications
(260 citation statements)
references
References 26 publications
2
249
1
8
Order By: Relevance
“…Similarly, the association of sorafenib and Y90RE did not result in a clear advantage in terms of progression-free survival being median PFS 6 vs. 7 months in Group 1 and 2 respectively (p = 0.992). These results confirm the findings of the aforementioned SORAMIC trial [19], thus strengthening the concept of the lack of benefit from combining the two treatments.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Similarly, the association of sorafenib and Y90RE did not result in a clear advantage in terms of progression-free survival being median PFS 6 vs. 7 months in Group 1 and 2 respectively (p = 0.992). These results confirm the findings of the aforementioned SORAMIC trial [19], thus strengthening the concept of the lack of benefit from combining the two treatments.…”
Section: Discussionsupporting
confidence: 87%
“…Despite the disappointing results of a large preliminary randomized controlled trial (RCT) [19], further studies are needed to properly evaluate the possible synergistic effects of the association of sorafenib and Y90RE. In particular, evidence on the comparison between Y90RE plus sorafenib versus Y90 alone is scarce, mainly provided only by a single RCT conducted in the pre-transplant setting, hence without the assessment of long-term survival outcomes [25,26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding combination therapy, the phase 2 prospective, randomized trial SORAMIC (98) compared Y-90 and sorafenib versus sorafenib alone for locally advanced HCC and showed similar median overall survival between groups (12.1 vs. 11.4 months, respectively). As the patient in case 2 has progressive disease with rising AFP despite two Y-90 treatments, transition to systemic therapy is most appropriate at this time.…”
Section: Case 2 Part Cmentioning
confidence: 98%
“…80 Similarly, the SORAMIC trial failed to illustrate a survival benefit of SIRT-sorafenib combined therapy in BCLC B to C patients not eligible for TACE. 81 When comparing SIRT to sorafenib in patients with HCC and portal invasion, a study examining 151 patients with HCC and portal vein tumor thrombus found an overall median survival benefit in patients treated with SIRT compared with sorafenib, 26.2 versus 8.7 months, respectively (HR 0.40, 95% CI: 0.19-0.82, p ¼ 0.013). The difference in OS was more pronounced in patients with branch portal vein thrombosis (as opposed to MPV thrombosis), with a respective median OS of 25.3 months (95% CI: 13.8-36.8) versus 7.0 months (95% CI: 5.2-8.9) (p ¼ 0.001), than in cases of main PVT, with a respective median OS of 12.0 months (95% CI: 4.6-19.3) versus 6.5 months (95% CI: 4.8-8.3) (p ¼ 0.195).…”
Section: Advanced Stage (C)mentioning
confidence: 99%